Scope of the Damaged Party under The Product Liability Act B.E.2551(2008) - Tanametanont, Voravut (Law for Development Graduate Journal, 2024)
The Product Liability Act B.E. 2551 (2008) was enacted on 20 February 2008 and has come into force since 20 February 2009 with an intention to protect the Damaged party or the consumer buying the products offered for sale in the market some of which may be unsafe and cause danger to or harm their life, body, health, sanitation, mind or property. Presently, almost all products produced or imported from abroad involve scientific knowledge, modern technology in their design or complicated production process. This has made it more difficult for the consumer to check if such products are safe and to avoid potential damage or dander. Moreover, to pursue legal remedy against unsafe product, the existing legal system, the civil case system, is quite complicated as we are required to adduce the evidence to prove the intention or negligence of the manufacturer or importer. Burden of proof is thus vested in the Damaged party based on the principle of contract or tort. Because this existing legal system cannot adequately remedy the Damaged party in the age of mass production with advanced technology, Thailand needs to enact The Product Liability Act B.E. 2551 (2008) by applying the principle of strict liability to the extent that the injured is not required to prove the unsafe nature of the product and this burden of proof has shifted to the manufacturer while fair amount of damages are reviewed and prescribed. According to additional review of The Product Liability Act B.E. 2551 (2008), the author has discovered certain ambiguity as to the scope of the Damaged party. Question has arisen if only the consumer is protected when buying or using unsafe project or this Act also covers other Damaged party who is the third party or not a consumer suffering from damage form such unsafe product. When considering the definition of the term “Damaged party” as provided in Section 4 of the said Act, it seems to cover all parties suffering from damage from unsafe product whether such person is a consumer or the third party. By linking with the intention of the Act, it, however, suggest that the provisions of this Act cannot well reflect such definition. Several provisions in certain Sections seem to mention about the consumer only and imply that this law aims to provide protection for the consumer only such as the burden of proof of Damaged party or his prosecuting representative. The author therefore proposes that certain provisions should be amended to be in line with the definition of the Damaged party and to help complete The Product Liability Act B.E. 2551(2008) that should provide protection for the consumer and actual Damaged party who may not be a consumer by drafting The Product Liability Act (No...) B.E. ....